Liquidity, activity and leverage ratios effect on profitability in Bursa Malaysia: Consumer product companies (2001-2005) / Norhafizah Kamisan - Kamisan, Norhafizah (2006)
ms paper seeks to investigate the correlation between the profitability, liquidity, leverage, and activity of consumer product listed companies on the Bursa Malaysia during a five year period which is from year 2001 until year 2005. This study focuses on the 60 consumer product companies listed on the Bursa Malaysia, which is under Main Board of the Bursa Malaysia. Basically, the purpose of this study is to determine whether there is any significant relationship between variable of profitability and those three variables which are liquidity, leverage and activity ratios. The data will be analyzed in the time series basis of annually data from year 2001 to year 2005. Bivariate correlation analysis is used in order to know the existence of correlation between profitability, liquidity, activity, and leverage ratios of selected consumer product companies listed on the Main Board of the Bursa Malaysia. This study found that there are significant effects of liquidity, activity and leverage ratios on profitability. It shows the overall performance of the companies based on financial ratios which are profitability, liquidity, leverage and activity ratios.